ACTN3 single nucleotide polymorphism is associated with non-contact musculoskeletal soft-tissue injury incidence in elite professional football players - Clos, Enric; Pruna, Ricard; Lundblad, Matilda; Artells, Rosa; Esquirol Caussa, Jordi (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2019)
Purpose Muscle injuries are common in professional football, even though prevention protocols are being implemented. Genetics constitutes a novel field for studying intrinsic injury risks and performance. Since previous studies involving single nucleotide polymorphisms (SNPs) have shown that SNPs influence muscle injury rate, injury severity and recovery time, the aim was to study the association the SNP of ACTN3 has with those parameters in professional football players. Methods The medical staff team recorded non-contact musculoskeletal soft-tissue injuries in 43 professional football players in 7 different seasons (2007–2012 and 2015–2016). Injury rate, injury severity and injury recovery times were established. Players were genotyped by extracting DNA from a blood sample and using a polymerase chain reaction. Results Injury rate was associated with the SNP of ACTN3 ( p = 0.003). The 577R allele was more frequent in subjects than in a normal population by showing presence in 93% of the subjects and suggesting that it could influence football performance. No statistically significant differences in injury severity and recovery time were associated with the SNP of ACTN3. Conclusions Genetics is gaining in importance when assessing injury risk and performance in professional football. ACTN3 can be regarded as a biomarker of injury susceptibility in this discipline. Identifying those players with the highest injury susceptibility through genetics could lead football teams to individualise workloads and prevention protocols. Level of evidence III.